Summary of feedlot performance and digestibilities of steers fed 13 hybrid sorghum and 2 hybrid corn grains - McCollough, R.L. (Kansas State University. Agricultural Experiment Station, 2011)
Two years and 270 head of steers were used to determine the feeding value of 13 hybrid sorghum grains and 2 hybrid corn grains fed in dry-rolled high-concentrate rations fed to finishing steers. The 15 corn and sorghum hybrids represented 7 endosperm types: hetero-yellow, white, all-waxy (amylopectin-type starch), part-waxy, and bird-resistant endosperm sorghum grains, regular yellow dent corn and high-oil corn. The grains ( 9 hybrids in each of 2 years and 3 hybrids replicated between years) were produced in the same field, and conditions were similar for each year and each hybrid. Each year, 15 head of steers were fed 126 days on each hybrid. Digestibilities were determined with 5 head of steers fed per hybrid in sheltered concrete lots, using chronic oxide.
Keywords: Beef; Feedlot performance; Steers; Hybrid sorghum; Hybrid corn